Women’s views on moderate and low alcohol consumption: stages of the subjective transition from pregnancy to postpartum - Jessica Pehlke-Milde; Irina Radu; Solène Gouilhers; Raphaël Hammer; Yvonne Meyer (BMC Pregnancy and Childbirth, 2022)
Abstract Background Alcohol consumption during pregnancy and breastfeeding is associated with a risk for the child’s healthy development. Nevertheless, about 16 to 25% of all women in the European region, including Switzerland, consume alcohol during pregnancy and probably even more during breastfeeding. Little is known about how women perceive this risk and how risk perception changes during the transition to motherhood. The present study aims to explore the subjective transition from the woman’s perspective, focusing on perceptions of alcohol as a risk, changes in alcohol consumption in daily life and experienced support from health professionals in this period. Methods The longitudinal qualitative, semi-structured interview study was jointly designed and conducted by health sociologists and midwifery researchers. Using the theoretical framework of sociocultural risk and life course transition, we interviewed 46 women from the French and German speaking part of Switzerland during pregnancy and until six months after birth. Results In our study, we found that pregnant and breastfeeding women perceive alcohol consumption as a risk to the health of the child. Abstinence is sought especially during pregnancy, but this does not preclude occasional and low-level consumption according to some women. Alcohol consumption and risk perception change during the transition to motherhood. We identified five stages that characterise this transition in terms of alcohol consumption and risk perception. From the women’s perspective, there was a lack of counselling from health professionals, and the women expressed a desire for respectful and more individualised counselling. Conclusion Many women express a need for guidance and counselling by health care professionals at some stages of the transition to motherhood. The stages identified can be used as pointers to address the subject of alcohol consumption in professional practice. The stage around conception and early pregnancy should be taken more into account, as women experience themselves as particularly vulnerable during this time. Low-threshold counselling services should be therefore offered to women before or in the stage around conception and be continued until the end of the breastfeeding period.